2005
DOI: 10.1002/cncr.21020
|View full text |Cite
|
Sign up to set email alerts
|

Differences in tumor core distribution between palpable and nonpalpable prostate tumors in patients diagnosed using extensive transperineal ultrasound‐guided template prostate biopsy

Abstract: BACKGROUNDThe authors performed extensive transperineal ultrasound‐guided template prostate biopsies to investigate carcinoma core distribution.METHODSBetween August 2000 and May 2004, 371 men underwent template biopsies. Three hundred twelve patients had not undergone a previous biopsy (first group) and 59 had undergone previous transrectal sextant biopsies (repeat group). Of the 312 patients in the first group, 236 had normal digital rectal examination (DRE) findings (DRE– first group) and 76 patients had an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
31
1
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 18 publications
5
31
1
1
Order By: Relevance
“…[7][8][9][10][11] To be noted, studies using extended TP biopsy protocols have revealed a different cancer core distribution according to the DRE finding. 9,11 Our recent finding that the cancer cores detected by a transrectal ultrasound (TRUS)-guided systematic TP 14-core biopsy distribute apicoanteriorly in stage T1c disease compared with stage T2 disease suggests a potential advantage of TP approach in detecting nonpalpable apicoanterior cancer foci. 9 As far as we know, there has been no study demonstrating a diagnostic advantage of the combination of TR and TP approaches over the single TR or TP approach.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11] To be noted, studies using extended TP biopsy protocols have revealed a different cancer core distribution according to the DRE finding. 9,11 Our recent finding that the cancer cores detected by a transrectal ultrasound (TRUS)-guided systematic TP 14-core biopsy distribute apicoanteriorly in stage T1c disease compared with stage T2 disease suggests a potential advantage of TP approach in detecting nonpalpable apicoanterior cancer foci. 9 As far as we know, there has been no study demonstrating a diagnostic advantage of the combination of TR and TP approaches over the single TR or TP approach.…”
Section: Introductionmentioning
confidence: 99%
“…3 When compared to TR biopsy, studies on extended transperineal (TP) biopsy have been relatively limited and there has been no consensus on standard extended TP biopsy protocol. [4][5][6][7][8][9][10][11][12][13] The lack of standardization at the moment is related to both TP and TR approaches.…”
Section: Introductionmentioning
confidence: 99%
“…They also reported a rate of 4.6% erectile dysfunction 1 month after TPSB, using the IIEF-6 score. Results from other studies are shown in table 2[12,13,14,15,16,17,18,19]. However, a majority relate to retrospective assessments made at 3-4 weeks.…”
Section: Discussionmentioning
confidence: 99%